A choreographed Sinophobia? An analysis of China's identity from the perspective of Zambia's Patriotic Front. Issue 1 (2nd January 2020) - Matambo, Emmanuel
ABSTRACT: China's identity in Zambia has been constructed in polarizing terms depending on the political and social standing of Zambians from political parties, civil society to ordinary citizens. The current paper looks at how the Patriotic Front (PF), from its time as an opposition to its time as a governing party, has constructed China's identity. The ill-will towards China that the PF constructed in its opposition days is described here as Sinophobia, a fear of China, the likely consequences of its investment and the presence of Chinese nationals. The paper traces how the PF (as an opposition party) moved from being a critic of China to being a staunch defender of China and Zambia-China relations (as ruling party). The conclusions drawn are that while Sinophobia was constructed, the fears expressed by the PF during its opposition days were justifiable and have become even more significant with the deepening of Zambia-China economic relations. Furthermore, the paper argues that current hostile positions towards China by opposition parties in Zambia reinforce the argument that China is an opportune pretext for those who hope to win the support of ordinary Zambians, who endure the perceived threat that comes with Chinese investment and Chinese employers and entrepreneurs. The paper relied mainly on Zambian media, government reports and legislation documents, the author's empirical study on China's identity and interest in Zambia and scholarly secondary literature as sources of data.